2022
DOI: 10.1101/2022.12.22.22283779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study of thyroid-stimulating hormone highlights new genes, pathways and associations with thyroid disease susceptibility and age-of-onset

Abstract: Thyroid hormones play a critical role in regulation of multiple physiological functions and thyroid dysfunction is associated with substantial morbidity. Electronic health records were used to undertake the largest genome-wide association study of thyroid-stimulating hormone (TSH) levels, with a total sample size of 247,107. We identified 158 novel signals, more than doubling the number of known associations with TSH, and implicating 112 putative causal genes, of which 78 were not previously implicated. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We observed no genome-wide genetic correlations between any category of female infertility and: (i) any reproductive hormone in this study, or (ii) thyroid stimulating hormone (TSH), or (iii) anti-Mullerian hormone (AMH), the latter two based on publicly available summary statistics 74,75 (all P>0.05, Figure 3B). Mendelian randomisation (MR) analyses indicated a genetically causal protective effect of FSH on risk of F-ALL (OR (95% CI)=0.776 (0.678-0.888), P=2.15E-04) and F-EXCL (0.716 (0.604-0.850), P=1.26E-04) (Supp.…”
Section: Genetic Relationships Between Female Infertility Reproductiv...mentioning
confidence: 62%
See 1 more Smart Citation
“…We observed no genome-wide genetic correlations between any category of female infertility and: (i) any reproductive hormone in this study, or (ii) thyroid stimulating hormone (TSH), or (iii) anti-Mullerian hormone (AMH), the latter two based on publicly available summary statistics 74,75 (all P>0.05, Figure 3B). Mendelian randomisation (MR) analyses indicated a genetically causal protective effect of FSH on risk of F-ALL (OR (95% CI)=0.776 (0.678-0.888), P=2.15E-04) and F-EXCL (0.716 (0.604-0.850), P=1.26E-04) (Supp.…”
Section: Genetic Relationships Between Female Infertility Reproductiv...mentioning
confidence: 62%
“…We estimated genetic correlations among the three categories of female infertility with significant heritability ( Z >4) 51 : F-ALL, F-ANOV, and F-INCL, as well as among heritable female reproductive hormones (FSH and testosterone in females). We additionally obtained summary statistics from GWASs of thyroid stimulating hormone (TSH) 75 (sex-combined analysis, N=247,107 participants) and anti-Mullerian hormone (N=7,049 pre-menopausal participants) 74 from the largest publicly available European-ancestry studies to date. We also tested for genetic correlations between infertility and reproductive hormones.…”
Section: Methodsmentioning
confidence: 99%
“…Consistency between the two hospitals involved examining the consistency of the effect direction of the lead SNPs and assessing the significance of the GWAS P-values in the Baoan and Longgang Studies. On the other hand, consistency of our meta-GWAS results and external datasets involved examining the consistency in an independent dataset from three separate cohorts (ThyroidOmics Consortium, the GWAS meta-analysis of Alexander T Williams et al, the GWAS meta-analysis of M. Medici et al) [10,11,34] . Beyond the participants previously referenced, our research included 4,688 individuals who attended Baoan District Maternal and Child Health Hospital for maternity check-ups during their 40-week gestation.…”
Section: Consistency and Replicationmentioning
confidence: 99%
“…Twin and family studies estimate heritable contributions to approximately 64%-70.8% for serum TSH, 39%-80% for FT4 [7][8][9] , and 48.8% for anti-thyroid peroxidase antibody (TPOAb) [9] . Large-scale meta-genome-wide association studies of thyroid hormones among general European populations have identified lead SNPs explaining 22.8% of TSH variation and 4% of FT4 variation, respectively [10,11] . These studies suggest that genetics may also influence thyroid function measurements during gestation, an aspect that has been under-studied.…”
Section: Introductionmentioning
confidence: 99%